(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
In this paper, a compact dual-band circular polarization (CP) multiple input multiple output (MIMO) antenna is proposed that can be used for 5G and wearable applications. The proposed antenna comprises two rectangular radiators used to obtain the dual-band response. The defected ground approach is used to mitigate the effect of surface current between the ports. Two open-ended stubs with T-shaped decoupling are used to improve the isolation between the ports without affecting the antenna parameters and the radiation pattern. The distance between two radiators is 0.31 λ0 which causes the high mutual coupling between the antennas. The two symmetric open-ended stubs are introduced to improve the isolation up to 17 dB at higher operating frequencies and are responsible for circular behavior. A T-shaped stub is inserted in the ground that improves the isolation up to 10 dB at a lower frequency. The dual-band response of the proposed antenna is observed from 3.0 GHz to 3.6 GHz covers 5G (n78) and 5.7 GHz to 9.7 GHz, which covers direct sequence (DS) ultra-wideband (UWB), smartphone, wearable, and biomedical applications. The proposed antenna shows circular behavior in the ISM band therefore, the proposed SAR is simulated and analyzed for wearable and cancer detection applications.